Risk Factors for Stroke-associated Pneumonia: A Prospective Cohort Study - Alexis Suárez Quesada; Ezequiel López Espinosa; Noelsis García Verdecia; Miguel Ángel Serra Valdés (Revista Finlay)
Background: stroke-associated pneumonia prolongs hospital stay and is an important risk factor for morbidity and mortality. Objective: to determine risk factors for stroke-associated pneumonia. Methods: a prospective single-cohort study was conducted involving 390 patients aged 16-93 years who met clinical and neuroimaging criteria for acute stroke treated at the Carlos Manuel de Céspedes Hospital from January 2012 through March 2015. Univariate comparison of qualitative variables was performed by using the Kaplan-Meier method. The Cox regression model was applied for multivariate analysis of risk factors for pneumonia. The area under the ROC curve was used to determine the discriminatory power of the model. Results: two hundred thirteen patients (54.6 %) with ischemic stroke and 177 (45.4 %) with hemorrhagic stroke were studied. Cases of nosocomial pneumonia after acute stroke accounted for 25.4 %. Subjects who developed pneumonia had lower scores on the Glasgow scale and higher scores on the modified Rankin scale. The following risk factors were identified using the Cox regression model: Glasgow coma score (Exp (B): 0.687; 95 % CI 0.630 to 0.750) and stroke subtype (Exp (B): 1.723; 95 % CI 1.137 to 2.610). The area under the ROC curve was 0.88. Conclusions: the risk factors for the development of nosocomial pneumonia after acute stroke found were the level of consciousness and suffering a hemorrhagic stroke. Other influencing variables are chronic obstructive pulmonary disease and heart disease as a comorbid condition.